The New Grove Dictionary of Women Composers - Sadie, Julie Anne; Samuel, Rhian (USA Macmillan, 1994)
The few in earlier times who gained some renown were as often as not the sisters, daughters, wives, or muses of well-known men?the surnames of Fanny Mendelssohn and Clara Schumann speak for themselves. Even with the present-day increase in their number, women composers have largely failed to draw the attention of the public.In recognition of these nearly invisible yet greatly talented musicians, Julie Anne Sadie and Rhian Samuel have brought together an international corps of experts to produce The Norton/Grove Dictionary of Women Composers. This definitive source provides detailed biographies of more than 1,000 creators of Western classical music. In signed articles, the Dictionary chronicles the lives and works of women composers from all corners of the world. Here you can read about the Medieval mystic Hildgard von Bingen, the Renaissance madrigalist Maddalena Casulana, the flamboyant seventeenth-century vocal composer Barbara Strozzi, the prolific New Englander Amy Beach, and the Pulitzer Prize winner Ellen Taaffe Zwilich.Show More Show Less
Keywords: Past; Encyclopedia; Composer; Female; Biography; World